Peran Widyaiswara dalam Strategi Pengembangan ASN “Corporate University” - Nurhikmah Nurhikmah (Universitas Mataram, 2020)
This paper discusses the development of the State Civil Apparatus competencies through an integrated learning system (Corporate University). Widyaiswara as a civil servant who has the task, responsibility, authority, and right to carry out these activities, and the evaluation of the Education and Training must take an important role in the ASN Corpu, especially the development of non-classical training. The ASN Corpu method emphasizes the 70-20-10 learning model. This research is qualitative in nature by exploring and describing the form of application of a corporate university, especially in the regions. This paper uses data sources, namely literature, regulations, interviews, and the author's experience of being involved in the knowledge sharing community which is part of the practice of building integrated competencies development methods. The results showed that the Corpu ASN method and the development of information technology encouraged job enlargement and job enrichment by widyaiswara. Widyaiswara's role is very important in building talent management, which will have an impact on achieving strategic goals for regional development and improving the quality of public services. The prerequisites for realizing this are an understanding of the vision and mission of the organization and the region, the collaboration and synergy built by various stakeholders, and the ability to manage knowledge through knowledge management.